Genetic relationships between interspecific lines derived from Oryza glaberrima and Oryza sativa crosses using microsatellites and agro-morphological markers - Moukoumbi, Yonnelle D.; Kolade, Olufisayo; Drame, Khady N.; Sie, Moussa; Ndjiondjop, Marie Noelle (Spanish Journal of Agricultural Research, 2015)
New Rice(s) for Africa (NERICA) are high yielding rice varieties mostly cultivated in Sub-Saharan Africa and developed by the Africa Rice Center. This study is aimed at investigating the proportion of introgression of parental genomic contribution of 60 lowland NERICA varieties and establishment of molecular profiling. Agro-morphological data from 17 characteristics was recorded and significant (p<0.05) to high significant (p<0.0001) differences were obtained with leaf length and width, plant height at maturity, days to heading, maturity, primary and secondary branching of panicles, and grain width and grain thickness. A total of 114 microsatellite polymorphic markers covering 2183.13 cM of the rice genome showed the proportions of alleles introgressed from the donor parent (Oryza glaberrima) into 52 lowland NERICA lines (TOG5681 and IR64) as follows: 11% for BC2, 6.07% for BC3, and 7.55% for BC4. The introgression proportions for the eight remaining lowland NERICA lines derived from other crosses ranged from 5.5 to 11.3%. The proportion recorded with the recurrent parent was 83.99%. The highest introgression proportions of the O. glaberrima allele for all 60 lowland NERICA lines were found on chromosomes 2, 6 and 12 (TOG5681/IR64) and on chromosome 3 with NERIC-L-29 (TOG5681/IR1529-680-3-2). Multivariate analyses performed using an association of agro-morphological and molecular data revealed two major groups according to the distribution of the lowland NERICAs including the lowland NERICAs released were found in cluster 1 of the dendrogram. Genetic and genomic studies, QTL identification and analysis using agro-morphologically significant traits revealed should be used to develop mega-varieties adapted in rice growth conditions in Sub-Saharan Africa.